A CLINICAL OBSERVATIONAL STUDY OF VIRECHANA KARMA IN MANAGEMENT OF AMLAPITTA - Aanal K Handa; Kalapi B Patel (International Journal of Applied Ayurved Research, 2018)
Background: Amlapitta is a very common disease of Annavaha Srotasa caused by Vidagdha Pitta with features such as Amlodgara, Hrid Kantha Daha, and Avipaka. Irregular and improper food habits and busy stressful lifestyle are main causes. Due to bad habit of taking unhealthy food, improper life style, the prevalence of Amlapitta is increased in present era. Objectives: The aim of this study is to find out effects of Shodhana treatment in the patients of Amlapitta. Methods: In this study total 20 patients were selected. All the signs and symptoms of the Amlapitta were given a grade scores and assessed the patient before and after the treatment. Statistical analysis was performed with use of ‘t’ test. Results: Highly significant improvement was noted in most of the signs and symptoms with more than 65% reduction. No any unwanted effects noted in any patient. Conclusion: Virechana karma is an effective therapy in management of Amlapitta as the main dosha involved is Pitta and Virechana is ideal treatment for elimination of vitiated Pitta and it also expels the Kapha Dosha. After Virechana Karma recurrence ratio of Amlapitta has been decreased. Pathya also plays an important role in the management of Amlapitta.